TEACHERS’ UNDERSTANDING IN IMPLEMENTING DIFFERENTIATION IN A SCHOOL FOR GIFTED STUDENTS IN KAZAKHSTAN - Bolsynova, Maira (Nazarbayev University Graduate School of Education, 2024)
Differentiated instruction is an educational method used to modify the learning experiences of students to suit their diverse needs and learning styles. The implementation of differentiated instruction has gained significance in the participating educational site in Kazakhstan because of continuous educational changes and the presence of diverse learners. This qualitative research aimed to better understand the viewpoints and practices used by teachers at a Kazakhstani school for gifted students through individual semi-structured interviews and non-participant lesson observations. A total of seven teachers were selected using purposeful sampling to participate in the interviews. Teachers from various departments of the school, including English, GPPW, Maths, Biology, Physics, and ICT, were individually interviewed and their lessons were observed. The findings of the study indicate that participants hold diverse opinions regarding differentiated instruction. Certain educators view it as an approach to foster learning opportunities through the accommodation of various learning styles, interests, and needs. Other teachers opt for differentiated instruction by offering students choices and forming groups based on their individual ability levels. Schoolteachers typically employ assignments of varied difficulty levels. The research findings may empower teachers to offer potential strategies to be implemented in schools in Kazakhstan, and specifically motivate in- service teachers and pre-service teachers to make adjustments in their teaching and learning approaches. The study concluded by making recommendations to school administrations and teachers on how to improve teachers’ expertise in implementing differentiated instruction.
Keywords: Type of access: Restricted; differentiated instruction; professional development; teacher knowledge; gifted students; Kazakhstan